Anaerobic Digestion Combined with Electrolysis of Poultry Manure and Activated Sludge Inoculum - Chernysh Y.Yu.; Shtepa V.N.; Plyatsuk L.D.; Chubur V.S.; Danylov D.V. (Problems of the Regional Energetics, 2022)
The aim of the work was to study the effect of electrolysis on the process of anaerobic digestion in the example of poultry manure with an inoculum of activated sludge from a municipal wastewater treatment plant. The set aim was achieved by solving the following tasks: microcopy of anaerobic activated sludge during the digestion of poultry manure under the influence of electrolysis treatment; studying the dynamics of biogas yield and its component composition under electrolysis treatment; studying the change in pH values and redox potential (ORP) in experiments with a combination of a bioreactor with electrolysis treatment and without treatment. Evaluation of the effect of stimulating the metabolic activity of microorganisms during treatment in the bioreactor-electrolyser was the most significant result. In addition, improved biodegradability of complex organic components of poultry manure was substantiated. Thus, methane yield on the 28th day was 640.5 ml from the total volume of 1525 ml of biogas, and under conventional conditions, methane yield was 33.4 ml from 50 ml of total volume. The decrease of H2S content in biogas under the influence of electrolysis was determined. A low ORP value of - 495 mV was achieved in the control experiment (without electrolysis treatment). ORP gradually increased in the bioreactor-electrolyser at all stages of digestion and reached -53 mV on day 28. pH stabilized at a neutral level. The positive effect of combining anaerobic digestion with electrolysis on the intensification of biogas production with a large volume of methane has been experimentally confirmed.